Identifying Populations at Risk: Interdisciplinary Environmental Climate Change Tracking. Issue 6 (16th October 2014) - Anderko, Laura; Davies‐Cole, John; Strunk, Andrew
Abstract Background Climate change, experienced as extreme weather events such as heat waves can lead to poorer air quality and underscores the critical need to consider the consequences of these environmental changes on health. Changes are occurring at a rate that exceeds what the world has experienced over the last 650, 000 years, yet little attention has been focused on the potentially catastrophic public health effects of climate change. Methods This study instituted a two‐phase approach. In building capacity for an Environmental Public Health Tracking Network, the District of Columbia Department of Health first examined the availability of climate change and health data. These data were then used to assess vulnerabilities and disease burden associated with heat, air quality, and hospitalizations for asthma (N = 5, 921) and acute myocardial infarction (AMI) (N = 2, 773) during 2007–2010. A Poisson regression analysis was applied to the time series of daily counts for hospitalizations for selected age, race, and gender groups. Results Although no significant associations were found for PM2.5, PM10, or ozone with asthma‐related or AMI‐related hospitalizations with seasonal changes, surveillance data found disparities in hospitalizations particularly in female, African American residents for both asthma and AMI. Conclusions Tracking Networks are critical for assessing community environmental health vulnerabilities.